Analysis of the Arabic Language Test Questions at the CELAD Institute from the Perspective of CEFR Standards - Alfitri; Musthofa, Tulus; Supriady, Harif (Institut Agama Islam Negeri Curup, 2025)
This study aims to describe and analyze the Arabic language test items used at the CELAD Institute, which serves as an assessment tool to measure the Arabic proficiency of students in the Faculty of Islamic Studies at Universitas Islam Riau. Specifically, the research identified the characteristics of CELAD’s Arabic language test items and determined their alignment with Common European Framework of Reference for Languages (CEFR) proficiency levels. This study adopted a descriptive-qualitative design with a content-analysis approach. The findings indicate that: (1) CELAD’s Arabic language test items are integrative, communicative, and interactive in nature, and fall within the category of standardized tests that include proficiency and achievement assessments; and (2) the competency standards reflected in the test align with CEFR, corresponding to level B1 for reading skills and level A2 for speaking and writing skills. This research is expected to serve as an evaluative reference for stakeholders in the further development of the CELAD Arabic language test. Additionally, the findings may offer a model for the development of other Arabic language tests that have not yet been standardized using an international reference framework.